The Stability of the Demand for Money: Evidence from the Post-1973 Period: A Comment - Hafer, R. W.; Hein, Scott E. (The Review of Economics and Statistics, 1982)
Another point: Meeks says that we did not include a variable reflecting differences in economic structure. He tried urbanization, found that has no effect on the results, and states that this provides confirmation for the generality of our In fact, the original authors had examined the effect of urbanization, and found (as did Meeks) that did not alter the results. Hence was not mentioned in our article. We therefore do not understand how this provides additional confirmation of his results. A last point: Meeks speculates that it could be that the expenditure effects at other levels take the form of quality rather than quantity changes. But there are some data that rebut that speculation. In a study of school age population, enrollment rates, expenditures per student, and student-teacher ratios (the latter an index of the quality of education) Billsborrow concluded: The empirical results indicate that population growth has not been systematically associated with growth in enrollment rates nor in qualitative deterioration in the education systems of developing countries in the period 1950-1970 (1978, p. 229). In conclusion, we read the data as showing that in MDCs population growth depresses educational expenditures for students, but much less so or not at all in LDCs. We do not know why this difference in results occurs, but differences in the quality of data might play a role. In future work, Meeks' specification of income per adult should be used.